Woman, object and memories: reflections on an artistic experience (Móin-Móin Magazine - Studies in the Art of Puppetry, 2020)
This article reflects on the relationship between two concepts: object and memory. Itapproaches the object not only from the manipulation but from the link that is established with thesubject when she is an activator of memories. The object is approached from its autonomy andin relation to the artist who works with it. The object as a bearer of memories is analyzed in thatliminal zone between theater of objects and performance. This reflection is accompanied by thethoughts of artists/researchers, among which Violeta Luna, Ana Amaral and Ana Alvarado standout. The approach is carried out from the perspective of an immigrant granddaughter, as thebearer of disputed memories.